A pseudo–index approach to fractional equations - Bartolo, Rossella (My University, 2015)
We study the multiplicity of weak solutions of a quasilinear elliptic problem on an open bounded domain of RN with smooth boundary ∂ Ω. Both the non– resonant and the resonant case are analyzed. Furthermore, we consider an analogous problem for the fractional p–Laplacian and on RN .
Keywords: Ecuaciones diferenciales elípticas; Elliptic problems; PDE